2019
DOI: 10.1101/588350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prenatal exposure to perfluoroalkyl substances modulates neonatal serum phospholipids, increasing risk of type 1 diabetes

Abstract: In the last decade, increasing incidence of type 1 diabetes (T1D) stabilized in Finland, a phenomenon that coincides with tighter regulation of perfluoroalkyl substances (PFAS). Here, we quantified PFAS to examine their effects, during pregnancy, on lipid-related and immune markers of T1D risk in children. In a mother-infant cohort (264 dyads), high PFAS exposure during pregnancy associated with decreased cord serum phospholipids and progression to T1D-associated islet autoantibodies in the offspring. This PFA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…Metabolic modelling of sphingolipid metabolism in islet autoimmunity and type 1 diabetes Given that (1) in our previous study, we observed persistent downregulation of plasma sphingolipids in children who progressed to type 1 diabetes [16,42], (2) in the present study, SMM was over-represented in PBMCs isolated from the PT1D, and (3) we recently found that prenatal chemical exposure modulates postnatal SM levels and increases type 1 diabetes risk [9], we examined SMM in PBMCs using genome-scale metabolic modelling (ESM Fig. 10).…”
Section: Metabolic Associations Between Immune Cells and Circulating supporting
confidence: 58%
See 1 more Smart Citation
“…Metabolic modelling of sphingolipid metabolism in islet autoimmunity and type 1 diabetes Given that (1) in our previous study, we observed persistent downregulation of plasma sphingolipids in children who progressed to type 1 diabetes [16,42], (2) in the present study, SMM was over-represented in PBMCs isolated from the PT1D, and (3) we recently found that prenatal chemical exposure modulates postnatal SM levels and increases type 1 diabetes risk [9], we examined SMM in PBMCs using genome-scale metabolic modelling (ESM Fig. 10).…”
Section: Metabolic Associations Between Immune Cells and Circulating supporting
confidence: 58%
“…In addition to genetic predisposition, other exogenous environmental factors affect risk, such as intestinal dysbiosis, reduced gut microbial diversity [5], level of hygiene [6] and infant-feeding regimen [7,8] are implicated in the initiation of beta cell autoimmunity. Our recent data also suggest that prenatal exposure to environmental chemicals modulates lipid metabolism in newborn infants and increases their subsequent risk of type 1 diabetes [9]. However, the early pathogenesis of type 1 diabetes is still poorly understood and of the molecular signatures and related pathways predictive of progression to overt type 1 diabetes have yet to be identified.…”
Section: Introductionmentioning
confidence: 89%
“…A counterintuitive dysregulation pattern where 11 BAs were dysregulated in high exposure versus low exposure groups compared to only two dysregulated bile acids in high exposure vs control group may be explained by the observation that in the low exposure group, BAs showed upregulation trend, whereas in the high exposure group they were signi cantly downregulated (Supplementary Figure A3), suggesting a non-monotonic response pattern. Observed alteration of bile acids in our study may explain the dysregulation of speci c lipid classes that were associated with T1D development in human studies (Oresic et al, 2008;McGlinchey et al, 2020).…”
Section: Discussionmentioning
confidence: 61%
“…Conversely, elevated PFOS levels were reported in young patients newly diagnosed with T1D (Predieri et al, 2015), while another birth-cohort study found no evidence that fetal and early life exposure to POP (including 14 PFAS) was a signi cant risk factor for later T1D development (Salo et al, 2019). Other studies suggest that PFAS exposure is associated with hyperglycemia, serum HDL cholesterol and increased blood insulin (Lin et al, 2009), may lead to immunotoxicity (Borg et al, 2013), and modulates neonatal serum phospholipids associated with increased risk of T1D (McGlinchey et al, 2020). Overall, the molecular mechanisms underlying the effects of exposure are still not well characterized.…”
Section: Introductionmentioning
confidence: 98%
“…Interaction between human leukocyte antigens risk genotype and pre-natal PFAS exposure was highlighted as to play a potential role in altered lipid profiles in newborn infants at-risk of developing T1D. 76 …”
Section: Resultsmentioning
confidence: 99%